IMPLEMENTATION OF DEEP LEARNING APPROACH IN THE FORMATION OF STUDENTS’ ISLAMIC CHARACTER AT STATE JUNIOR HIGH SCHOOL 3 PELEPAT ILIR - Moch Anwar Zaenudin; Andryadi; Ulfa Adilla (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
This study aims to analyze the implementation of the deep learning approach in Islamic Religious Education learning and its contribution to the formation of Islamic character of students at SMP Negeri 3 Pelepat Ilir. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of school principals, vice principals, PAI teachers, and students. The results of the study show that deep learning is applied through reflective learning and religious habits, such as congregational zuhur prayers, recitation readings, tahfiz, lectures, and Yasin readings, so that students are more active, easier to get along with material with real life, and better understand the value of honesty, discipline, responsibility, and the meaning of worship. The findings also show the growth of socio-religious interaction and students’ metacognitive awareness, although the implementation still faces obstacles in the form of time constraints, teacher readiness, variation in learning styles, and facility support. The novelty of this research lies in the placement of deep learning not only as a strategy to improve cognitive understanding but as an integrative approach that links classroom learning, personal reflection, and school religious culture in the formation of Islamic character. The implications of this study emphasize the importance of designing reflective PAI learning so that schools can strengthen the substantive internalization of Islamic values, build a dynamic religious culture, and make Islamic Religious Education a space for the transformation of students’ knowledge, attitudes, and behaviors in the era of inclusive contemporary education.